2006
DOI: 10.1128/aem.72.3.2185-2190.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transport at Ambient Temperature on Detection and Isolation of Vibrio cholerae from Environmental Samples

Abstract: It has long been assumed that prolonged holding of environmental samples at the ambient air temperature prior to bacteriological analysis is detrimental to isolation and detection of Vibrio cholerae, the causative agent of pandemic cholera. The present study was aimed at understanding the effect of transporting environmental samples at the ambient air temperature on isolation and enumeration of V. cholerae. For water and plankton samples held at ambient temperatures ranging from 31°C to 35°C for 20 h, the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…The absence of V. cholerae O1 in our samples may be due to the high prevalence of non-O1/non-O139 strains, which are believed to be indigenous members of the aquatic ecosystem and which can prevent isolation of the truly pathogenic strains [14]. Holding samples from freshwater ecosystems at an ambient temperature ranging from 31°C to 35°C for 20 hours before processing has been found to selectively increase the number of culturable vibrios [15].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of V. cholerae O1 in our samples may be due to the high prevalence of non-O1/non-O139 strains, which are believed to be indigenous members of the aquatic ecosystem and which can prevent isolation of the truly pathogenic strains [14]. Holding samples from freshwater ecosystems at an ambient temperature ranging from 31°C to 35°C for 20 hours before processing has been found to selectively increase the number of culturable vibrios [15].…”
Section: Discussionmentioning
confidence: 99%
“…A 24-hour holding time has been shown to be beneficial for V. cholerae culture. 15 Using multiple sample collection and analytical methods, toxigenic V. cholerae O1 was detected in Haitian water sources more than 2 years after the start of the cholera epidemic. The association of V. cholerae ctxA gene detections with higher E. coli concentrations and turbidity indicate that V. cholerae contamination may have been associated with inadequate sanitation and fecal runoff into water bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Water samples for V. cholerae testing were held in a cooler at ambient temperature for 24 hours to improve detection by culture. 15 Some samples were held for 48 hours before processing as a result of logistical constraints.…”
Section: Methodsmentioning
confidence: 99%
“…The two areas under study were reported previously by Alam et al (1,2). Briefly, Bakerganj is located in the southern district of Barisal, about 70 km north of the coast of the Bay of Bengal and approximately 300 km southwest of Dhaka, the capital city of Bangladesh (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Also, during the process of filtration, 500 ml of filtrate from the 20-m net was collected and analyzed for planktonic (unattached, free-living) bacteria. Both water and plankton samples were transported at ambient temperature to the International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR, B), Dhaka, and processed within 12 to 16 h of collection (2).…”
Section: Methodsmentioning
confidence: 99%